Pre-service English Teacher’s Challenges in Public Speaking - Anggraini, Helni; Mahdum; Daud, Afrianto (PROJECT (Professional Journal of English Education), 2026)
This study aims is to identify public speaking challenges which are mostly faced by pre-service English teacher’s at FKIP Universitas Riau during the English Students Conference (ESC). The ESC, which is part of the public speaking course aims to assess students' speaking skills in formal, academic settings.The method used was quantitative descriptive research, with data collected from 32 seventh-semester students through a validated questionnaire containing 40 items. Internal factors included linguistic and psychological aspects, while the learning environment included external aspects. The results of this study indicate that anxiety is the most common challenge, at a high level, while vocabulary was the highest challenge in linguistic aspects. Other psychological challenges were at a moderate level, such as lack of motivation, shyness, fear of making mistakes, and lack of self-confidence. Fluency, grammar, pronunciation, and comprehension are linguistic issues that are also at moderate level. External factors show minimal impact, with the lowest score coming from an unsupportive classroom environment and peers. In conclusion, psychological factors, especially anxiety, are the main challenges to effective public speaking performance. This highlights the need for targeted strategies focusing on anxiety management, building self-confidence, and creating a supportive learning environment.